PERILAKU MEROKOK DI KALANGAN MAHASISWA DAN MOTIVASI MEREKA UNTUK BERHENTI - Sugiyo, Dianita (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Smoker’s motivation is essential to support the success of smoking cessation intervention by the chosen method. The percentage of active smokers in a university is 29.2%, and 303 people (77.6%) have moderate to high motivation to quit smoking. Objective: The study was aimed to measure student motivation to quit smoking and identify the factors that influencing them to start consuming cigarette. Methods: The study method was cross sectional using cluster simple random sampling for sampling method among 271 smoking students in eight different faculties. Results: Among the smoking students, most of them starts smoking when they were teens, in an age range of 12 to 15 years old. Peer influence was among the higher risk factor inviting them to initiate consuming cigarette. Conclusion: Smoking prevalence among youth was increased among other age, and the influence of social environment or peer group was the greatest among the other smoking factors. It is important to involve peer support group to help smokers in quitting smoking.